Supraglottic airway devices vs tracheal intubation in children: a quantitative meta‐analysis of respiratory complications. Issue 10 (30th July 2014) - Luce, Virginie; Harkouk, Hakim; Brasher, Christopher; Michelet, Daphné; Hilly, Julie; Maesani, Matthieu; Diallo, Thierno; Mangalsuren, Nyamjargal; Nivoche, Yves; Dahmani, Souhayl; Lerman, Jerrold
Summary Background Rate of perioperative respiratory complications between tracheal intubation (TI) and laryngeal mask airway remains unclear during pediatric anesthesia. Objectives The aim of the present meta‐analysis was to compare the perioperative respiratory complications between laryngeal mask airway and TI. Methods A meta‐analysis of available controlled studies comparing laryngeal mask airway to TI was conducted. Studies including patients with airway infection were excluded. Data from each trial were combined to calculate the pooled odds ratios (OR) or mean difference (MD) and 95% confidence intervals. Results The meta‐analysis was performed on 19 studies. In 12 studies, patients were given muscle relaxation, and in 16 studies, ventilation was controlled. During recovery from anesthesia, the incidence of desaturation (OR = 0.34 [0.19–0.62]), laryngospasm (OR = 0.34 [0.2–0.6]), cough (OR = 0.18 [0.11–0.27]), and breath holding (0.19 [0.05–0.68]) was lower when laryngeal mask airway was used to secure the airway. Postoperative incidences of sore throat (OR = 0.87 [0.53–1.44]), bronchospasm (OR = 0.56 [0.25–1.25]), aspiration (1.33 [0.46–3.91]) and blood staining on the device (OR = 0.62 [0.21–1.82]) did not differ between laryngeal mask airway and TI. Results were homogenous across the studies, with the exceptions of blood staining on the device. Conclusions This meta‐analysis found that the use of laryngeal mask airway in pediatric anesthesia results in a decrease in a number of common postanesthetic complications. It is therefore a valuable device for the management of the pediatric airway.